On Cyprian Norwid. Studies and Essays Vol. 2. Aspects - Chlebowska, Edyta; Brajerska-Mazur, Agata (Polish Studies - Transdisciplinary Perspectives, 2021)
The book is the second volume of an extensive four-volume monograph devoted to the work of Cyprian Norwid (1821-1883), one of the most outstanding Polish authors. The impact of Norwid's oeuvre does not fade, as he addresses fundamental and timeless issues, such as the moral and spiritual condition of man or his place in the world and history, and seeks to answer universal questions. The book contains an extensive selection of contributions by　eminent researchers, which represent different approaches to the poet's work. They cover various areas of research, including interpretation, thematology, genology, and editing.